Emerging Processing Technologies for the Recovery of Valuable Bioactive Compounds from Potato Peels - Emanuela Calcio Gaudino; Alessandro Colletti; Giorgio Grillo; Silvia Tabasso; Giancarlo Cravotto (Foods, 2020)
Potato peel (PP) is the major underutilised by-product in the potato-processing industry and a potential source of valuable bioactive molecules. Among them, glycoalkaloids and polyphenols are important precursors for steroid hormones and natural antioxidants, respectively. Moreover, the huge quantities of industrial potato-peel waste that are produced are a rich source of primary metabolites, which principally include starch as well as non-starch polysaccharides, proteins, lipids, lignin and cellulose. All carbohydrates are prone to undergo fermentation to produce ethanol, lactic and acetic acid. Finally, the main portion of PP is made up of alcohol-insoluble matter with a dietary fibre content of approximatively 40%. The present review summarises the recent advances and emerging technologies in potato-peel extraction and further valorisation processing in the food industry.